2017
DOI: 10.31018/jans.v9i4.1548
|View full text |Cite
|
Sign up to set email alerts
|

Determination of genetic divergence in pointed gourd by principal component and non-hierarchical euclidean cluster analysis

Abstract: Abstract:The present investigation was carried out at Vegetable Research Centre, Pantnagar to estimate the genetic divergence using Mahalanobis D 2 statistics for twelve characters on 35 genotypes of pointed gourd. Cluster analysis and principal component analysis (PCA) were used to identify the most discerning trait responsible for greater variability in the lines and on the basis of mean performance, genotypes were classified into different groups. Five principal components (PC) have been extracted using the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 12 publications
0
2
0
Order By: Relevance
“…Therefore, they should be considered in maize improvement program in derived savannah agroecology. Principal component analysis has been successfully used for explaining observed variations in germplasms of Vigna unguiculata (Ansah et al, 2016), Telfairia occidentalis (Chukwdi and Agbo, 2016), Cucumis sativus L. (Ene et al, 2016), pointed gourd (Verma et al, 2017).…”
Section: Principal Component Analysismentioning
confidence: 99%
“…Therefore, they should be considered in maize improvement program in derived savannah agroecology. Principal component analysis has been successfully used for explaining observed variations in germplasms of Vigna unguiculata (Ansah et al, 2016), Telfairia occidentalis (Chukwdi and Agbo, 2016), Cucumis sativus L. (Ene et al, 2016), pointed gourd (Verma et al, 2017).…”
Section: Principal Component Analysismentioning
confidence: 99%
“…Days to first female flowering, days to first male flowering, days to first fruit harvest and number of fruits per plant were exhibited the oppositional narrow from the graph (Fig 2) that PC1 exhibited the greatest variation compared to the other eleven PCs; consequently, the selection of lines for characters under PC1 may be desired. Verma et al (2017) also reported a similar curve line in pointed gourd accessions.…”
Section: Pca Analysismentioning
confidence: 57%
“…The remaining four (4) genotypes were equally distributed among the remaining four clusters. Verma et al (2017) in an experiment on pointed gourd categorized into seven clusters as per the D 2 value of thirty nine genotypes of pointed gourd. The present study indicated that the locational distribution of different genotypes were not related to genetic variation as the genotypes collected from same location were grouped into different distinct cluster.…”
Section: Resultsmentioning
confidence: 99%